Students' academic achievement and teachers' teaching effectiveness and personality traits: a correlation analysis - Bautista, Lilia Dino (Animo Repository, 1990)
This study determines the nature and degree of probable interrelationships among teachers' personality traits, teaching effectiveness, and students' academic achievement in the high school department of Concordia College during the school year 1988 to 1989. The descriptive-correlational research method was used in this study. There were two groups of respondents in this study. The first group consisted of 17 teacher advisers in the high school department of Concordia College in Manila. The second group consisted of the students of the respective advisory classes of the teacher respondents. For each teacher respondent, one class was randomly selected from those that the teacher handled. Two instruments were used in this study: the Teacher Behavior Inventory (TBI) constructed by Tang (1973) and the 16 Personality Factor Questionnaire. Descriptive statistics like frequencies, percentages, means and standard deviations, as well as correlational and regression analyses were used as statistical treatment and analysis of data. Based on the findings of the study, the following conclusions may be drawn: 1) The teachers of the respondent schools were generally effective based on the assessment of their students. In addition, they generally possessed personality traits which are deemed desirable of a teacher. 2) Teachers' teaching effectiveness and degree of humility and consideration can significantly account for differences in students' academic performance in the respondent school. 3) Factor E (humble vs. assertive) is the best predictor of teachers' effectiveness and the students' academic achievement. 4) Since teachers' personality traits and teaching effectiveness cannot account for the variance in the students' academic performance, there are other factors that are predictive of the given dependent variables.